Numerical study of combustion instabilities and low-temperature chemistry effects in premixed flames under internal combustion engine conditions - Meier, Rafael Becker (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2022